Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Self Regulated Learning Siswa - Musliha Musliha; Rena Revita (JRPM (Jurnal Review Pembelajaran Matematika), 2021)
This research aimed to know the effect of implementing the Problem Based Learning model toward students’ mathematical problem-solving ability derived from their self-regulated learning at MTs Rokan Hulu. This research using a factorial experiment design. By random cluster sampling, 8th-grade students of A-class as the experimental and C-class students as the control group. Data were collected from the mathematical problem-solving ability test and self-regulated learning questionnaire. The result of this study is: 1) there was a difference in mathematical problem-solving ability between students taught by Problem Based Learning model and those who educated by direct learning, 2) there was a difference in mathematical problem-solving ability among students having high, medium and low self-regulated learning, and 3) there was no interaction between Problem Based Learning model and student mathematical problem-solving ability.